Clarifications on democracy and economic planning: an engagement with Robin Hahnel. Issue 2 (4th May 2022) - Adaman, Fikret; Devine, Pat
Abstract: Models developed by Robin Hahnel and Pat Devine both claim to rest on democratic planning in an ecosocialist society. Whereas Hahnel depends on a neoclassical framework (commensurability of goods, assumption of homo economics, reliance on marginal costs-benefits), Devine relies on knowledge in different forms as articulated at the individual, institutional, and societal levels by the social owners at each level and incorporates a transformatory dynamic through which particular interests are negotiated into a socially constructed general interest. This paper is part of the "Democratic Economic Planning" theme.